2015
DOI: 10.4236/jct.2015.69088
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Breast Cancer Patients Underwent Surgery in a Developing Country

Abstract: Background: We aim to review different factors associated with the relapse and the mortality in breast cancer patients in restricted-resource settings over a five-year period. Method: A retrospective cohort study including 133 women underwent breast cancer surgery was performed at the Surgical Oncology Unit of the Conakry University Hospital in Guinea. Socio-demographical characteristics, clinical information, treatment and data on relapse and survival were retrieved from medical files. Predictor factors of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…This target therapy has been made possible through the use of monoclonal antibodies and hormone therapy. In our country, immunohistochemistry (IHC) is not available and there are very little data on the molecular profile of breast cancer [4, 9]. This study aimed to determine the first trends in the molecular profile of breast cancers followed at the surgical oncology unit of Donka National Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…This target therapy has been made possible through the use of monoclonal antibodies and hormone therapy. In our country, immunohistochemistry (IHC) is not available and there are very little data on the molecular profile of breast cancer [4, 9]. This study aimed to determine the first trends in the molecular profile of breast cancers followed at the surgical oncology unit of Donka National Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The stage at diagnosis was reported in 7/13 studies 25–27,30,33–36 ; histopathology data were found in all the studies except two, 25,35 and hormonal status in 5 out of 13 studies 26,27,30,33,34 . Data about the CT use were in all the studies except one 29 .…”
Section: Resultsmentioning
confidence: 97%
“…The group of “FBC surgical excision/reconstruction” studies was composed of 12 publications. The 5‐year overall survival (OS) or mortality rate were described in only one 25 ; two studies reported OS with a follow‐up less than 5 years, 26,27 and one reported the metastasis‐free survival data 26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations